Predictive value of growth differentiation factor-15 in patients with myocardial infarction - A. A. Sabirzyanova; A. S. Galyavich; L. V. Baleeva; Z. M. Galeeva (Российский кардиологический журнал)
Aim. To evaluate the prognostic value of growth differentiation factor-15 (GDF-15) in patients with acute myocardial infarction (MI).Material and methods. The study included 118 patients under the age of 70 with STand non-ST segment elevation myocardial infarction, who, in addition to routine examination, were tested for GDF-15 by enzyme-linked immunosorbent assay in the first 48 hours from the onset. The statistical significance of the differences in quantitative indicators was assessed by the Student’s t-test for a normal distribution and by the nonparametric U Mann-Whitney test for a non-normal distribution, while in qualitative indicators — by Pearson’s chisquared test. Pearson’s correlation coefficient and Spearman’s rank correlation coefficient were used as an indicator of strength of relationship between quantitative indicators.Results. The average GDF-15 level in patients with MI was 2,25±1,0 ng/ml. For 6 months of follow-up, 15,25% of patients were rehospitalized for unstable angina or recurrent myocardial infarction. The GDF-15 level in 82,6% of cases was in the third and fourth quartiles (≥2,07 ng/ml). All patients with recurrent MI had GDF-15 levels in the upper quartile (≥2б73 ng/ml). Patients with GDF-15 levels in the upper quartile had a significantly higher risk of rehospitalization (hazard ratio, 3,3 (95% CI, 1,65-6,76), p<0,05) compared with patients with GDF-15 levels in other quartiles. The potential for the combined use of GDF-15 and N-terminal probrain natriuretic peptide (NT-proBNP) levels to assess the risk of readmission has been evaluated. Patients who had both GDF-15 and NT-proBNP levels in the upper quartiles (GDF-15>2,73 ng/ml, NT-proBNP>1418 pg/ml) had 4,8 times higher risk of rehospitalizations for unstable angina or recurrent myocardial infarction.Conclusion. In patients with MI, the determination of the GDF-15 level has prognostic value and may serve as an additional marker of the risk of recurrent cardiovascular events.